Moderasi Beragama Dan Era Digital Sebagai Strategi Pengokohan Akidah Dan Penguatan Ekonomi Umat - Enceng Enceng Iip Syaripudin; Saep Saepudin; Deni Konkon Furkony; Gini Gaussian (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2024)
Religious moderation is an essential element in maintaining harmony within communities, particularly in the challenging era of digital transformation. This study aims to analyze the role of religious moderation as a strategy to strengthen faith and promote the economic development of communities amidst technological advancements. Utilizing a descriptive qualitative approach, the research collects data through several methods, including literature reviews of relevant sources, in-depth interviews with religious leaders and economic practitioners, and direct observation of activities grounded in religious values in digital spaces. The data is analyzed by linking empirical findings to the theories of religious moderation and Islamic economics while ensuring the validity of the results through data triangulation. The study reveals that strengthening faith can be achieved through the enhancement of religious moderation, supported by digital literacy, interinstitutional collaboration, and the utilization of technology for Sharia-based economic activities. The integration of religious moderation and digital innovation emerges as a strategic solution to address the spiritual and economic challenges faced by contemporary communities. Keywords: Religious Moderation, Digital Era, Faith, Community Economy, Digital Literacy